'A diabetic' versus 'a person with diabetes': the impact of language on beliefs about diabetes. Issue 3 (November 2013) - Ogden, Jane; Parkes, Kirstie
Abstract Many organisations avoid disease‐based labels such as 'diabetic' or 'epileptic' as they are believed to be detrimental to a patient's beliefs about their condition and may generate stigma. The aim of this study was to examine the impact of the term 'a diabetic' compared with the term 'a person with diabetes' on the beliefs of participants who either did or did not have the condition. The study used an experimental design and was in two parts, with study cohorts derived from Diabetes UK websites and the University of Surrey website. Part 1 evaluated the impact of the two terms – 'a diabetic' and 'a person with diabetes' – on participants who had diabetes, in relation to their beliefs about the condition, using the Revised Illness Perception Questionnaire. Part 2 measured the impact of these two terms on participants without diabetes in relation to their positive and negative stereotypes of the condition. Data were gathered for 92 participants with diabetes (Part 1) and for 99 participants without diabetes (Part 2). The results showed no significant differences between the term 'a diabetic' compared with the term 'a person with diabetes' on either the beliefs of people with diabetes or the stereotypical attitudes of people without diabetes. In conclusion, the results suggest that the two terms are not as different as has been sometimes assumed.